Structural prediction of graphitization and porosity in carbide-derived carbons. (August 2017) - de Tomas, Carla; Suarez-Martinez, Irene; Vallejos-Burgos, Fernando; López, María J.; Kaneko, Katsumi; Marks, Nigel A.
Abstract: Carbide-derived carbons (CDCs) are nanoporous carbons with a tunable pore size, making them desirable for their adsorption properties. Despite their applicability, reliable structural models are difficult to construct due to the interplay between strong short-range order and long-range disorder. Here, a mimetic methodology is developed to generate atomistic models of CDCs using Molecular Dynamics and the Environment Dependent Interaction Potential. This approach reproduces the main characteristics of experimentally-prepared CDCs, including microstructure, porosity at the nanometre scale, and graphitization with increasing temperature. An Arrhenius-based approach is used to bridge the timescale gap between Molecular Dynamics and experiment and build a connection between the simulation and synthesis temperatures. The method is robust, easy to implement, and enables a fast exploration of the adsorption properties of CDCs. Graphical abstract: